Preference of English Language Education Students of Learning Styles - Triananda, Anak Agung Ayu Novi (Journal of Educational Study, 2022)
Students bring their own unique characteristics during the learning process in the class. They have different ways of following the learning process itself. This way can be called preference or style. They will use the style that matches and help them in comprehending the learning material during the learning process. There is known that students' learning styles are divided into many kinds according to some experts. Therefore, this study aimed at investigating the prominent styles of EFL students using VARK Model by Neil Fleming. To gather the data, the study used a descriptive study with a survey. The participant in this study come from 20 English Language Education of Ganesha University students from the 7th semester. This study revealed that the prominent of students' learning preferences came from Multimodal style which were the combination between reading/write (R) and kinestheticstyle learners. Students who are learning with a read/write style like to demand information in the form of words or text. They like to read and taking notes while learning. Some visual-real aids like graphs, diagrams, etc., helped them a lot while learning. Meanwhile, for students with kinesthetic learning style, they tend to have a hands-on interaction for it is essential to them. The greatest ways for kinesthetic learners to learn is they like to directly do a physical touch while learning and like doing some authentic activity like practical exercises, trial and error activities, and solving some case studies.